The clinical evaluation of the triglyceride-glucose index as a risk factor for coronary artery disease and severity of coronary artery stenosis in patients with chronic kidney disease - Dan Liu; Xiaoyang Guan; Ruoxin Chen; Ci Song; Shanhu Qiu; Shengchun Xu; Jingyuan Cao; Hong Liu (Renal Failure)
Introduction Insulin resistance (IR) plays an important role in the occurrence and development of cardiovascular disease (CVD) in patients with chronic kidney disease (CKD). The triglyceride-glucose (TyG) index is a simple and effective tool to evaluate IR. This study aimed to evaluate the association of the TyG index with coronary artery disease (CAD) and the severity of coronary artery stenosis (CAS) in nondialysis patients with stages 3–5 CKD.Methods Nondialysis patients with stages 3–5 CKD who underwent the first coronary angiography at Zhongda Hospital affiliated with Southeast University from August 2015 to January 2017 were retrospectively analyzed. CAS was measured by coronary angiography, and the CAS score was calculated as the Gensini score. Logistic regression analysis was used to determine the related factors of CAD and severe CAS.Results A total of 943 patients were enrolled in this cross-sectional study and 720 (76.4%) of these patients were diagnosed with CAD. The TyG index in the CAD group (7.29 ± 0.63) was significantly higher than that in the non-CAD group (7.11 ± 0.61) (p < 0.001). Multivariate logistic regression analysis showed that a higher TyG index was an independent risk factor for CAD in CKD patients after adjusting for related confounding factors (OR = 2.865, 95% CI 1.681–4.885, p < 0.001). Patients in the CAD group were divided into three groups according to the Gensini integral quantile level. Multivariate logistic regression analysis showed that the TyG index was an independent related factor for severe CAS after adjusting for relevant confounding factors (p < 0.001).Conclusions The TyG index is associated with CAD and the severity of CAS in patients with nondialysis stages 3–5 CKD. A higher TyG index is an independent factor for CAD and severe CAS.